Case report: Perinephric lymphangiomatosis - Gorantla, Rajani; Yalapati, Anusheela; Dev, Bhawna; Joseph, Santhosh (Indian Journal of Radiology and Imaging, 2010)
Perirenal lymphangiomatosis is a rare benign malformation of the lymphatic system. We report here a case of bilateral perirenal and parapelvic involvement with a normal excretory collecting system.
Keywords: Perirenal lymphangiomatosis; perirenal collections; kidney